Simplistic understandings of farmer motivations could undermine the environmental potential of the common agricultural policy. (February 2021) - Brown, Calum; Kovács, Eszter; Herzon, Irina; Villamayor-Tomas, Sergio; Albizua, Amaia; Galanaki, Antonia; Grammatikopoulou, Ioanna; McCracken, Davy; Olsson, Johanna Alkan; Zinngrebe, Yves
Highlights: We compare literature and interviews on farmers' decision-making. Literature suggests a wide range of interacting factors affect farmer choices. Policy-maker interviews reveal a narrow focus on economic and structural factors. Simplistic design of environmental subsidies may limit uptake and effectiveness. Better understanding of farmer motivations can help achieve environmental goals. Abstract: The European Union Common Agricultural Policy (CAP) has failed to achieve its aim of preserving European farmland biodiversity, despite massive investment in subsidies to incentivise environmentally-beneficial farming practices. This failure calls into question the design of the subsidy schemes, which are intended to either function as a safety net and make farming profitable or compensate farmers for costs and loss of income while undertaking environmental management. In this study, we assess whether the design of environmental payments in the CAP reflects current knowledge about farmers' decision-making as found in the research literature. We do so on the basis of a comprehensive literature review on farmers' uptake of agri-environmental management practices over the past 10 years and interviews specifically focused on Ecological Focus Areas with policy-makers, advisors and farmers in seven European countries. We find that economic and structural factors are the most commonly-identified determinants of farmers' adoption of environmental management practices in the literature and in interviews. However, the literature suggests that these are complemented by – and partially dependent on – a broad range of social, attitudinal and other contextual factors that are not recognised in interview responses or, potentially, in policy design. The relatively simplistic conceptualisation of farmer behaviour that underlies some aspects of policy design may hamper the effectiveness of environmental payments in the CAP by over-emphasising economic considerations, potentially corroding farmer attitudes to policy and environmental objectives. We conclude that an urgent redesign of agricultural subsidies is needed to better align them with the economic, social and environmental factors affecting farmer decision-making in a complex production climate, and therefore to maximise potential environmental benefits.